1997
DOI: 10.1074/jbc.272.2.1323
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Platelet Activation and Aggregation by a Carboxyl-terminal Peptide from Thrombospondin Binding to the Integrin-associated Protein Receptor

Abstract: Thrombospondin, a major secretory product of the ␣-granules of activated platelets, is a large trimeric glycoprotein that plays an important role in platelet aggregation. On resting platelets, thrombospondin binds to a single receptor in a cation-independent manner, but upon platelet activation it binds at least two further, distinct receptors that are both dependent upon divalent cations. Each of these receptors on the platelet surface binds to different regions of the thrombospondin molecule, and such bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 45 publications
(32 reference statements)
3
51
1
1
Order By: Relevance
“…We detected a modest enrichment of genes involved in ''cell-to-cell signaling and interaction'' (range, P = 4.52 3 10 À2 to 1.17 3 10 À1 , Benjamini-Hochberg corrected for multiple testing; n = 10). Notably, these genes included THBS1 (encoding thrombospondin 1), WASL (Wiskott-Aldrich syndrome-like), and EDN1 (endothelin 1), which have a marked role in the activation of blood platelets (Dorahy et al 1997;Falet et al 2002;Jagroop et al 2005). This suggests the involvement of non-cell-autonomous mechanisms for the regulation of platelet count, whereby extrinsic factors expressed by MOs or their progeny regulate the differentiation and proliferation of the hematopoietic stem cells toward MKs and the removal of senescent platelets from the circulation by liverresiding MO-derived macrophages.…”
Section: Enrichment Patterns Of Snps Associated With Closely Related mentioning
confidence: 99%
“…We detected a modest enrichment of genes involved in ''cell-to-cell signaling and interaction'' (range, P = 4.52 3 10 À2 to 1.17 3 10 À1 , Benjamini-Hochberg corrected for multiple testing; n = 10). Notably, these genes included THBS1 (encoding thrombospondin 1), WASL (Wiskott-Aldrich syndrome-like), and EDN1 (endothelin 1), which have a marked role in the activation of blood platelets (Dorahy et al 1997;Falet et al 2002;Jagroop et al 2005). This suggests the involvement of non-cell-autonomous mechanisms for the regulation of platelet count, whereby extrinsic factors expressed by MOs or their progeny regulate the differentiation and proliferation of the hematopoietic stem cells toward MKs and the removal of senescent platelets from the circulation by liverresiding MO-derived macrophages.…”
Section: Enrichment Patterns Of Snps Associated With Closely Related mentioning
confidence: 99%
“…Under some conditions, TSP1 promotes platelet aggregation [92], but recombinant domains and peptides derived from TSP1 can either increase or delay platelet aggregation [93][94][95][96]. TSP1 also regulates the processing of the platelet adhesion factor von Willebrand factor (vWF) by ADAMTS13 [97], which is associated with increased collagen-and vWF-mediated aggregation of TSP-1 null platelets under static and shear conditions [98].…”
Section: Tsp1 Regulation Of No Signaling In Plateletsmentioning
confidence: 99%
“…12,16,17 In platelets, IAP is associated with ␣IIb␤3 and ␣2␤1 integrins that bind to fibrinogen and collagen, respectively. 15,18 It was reported that 4N1-1 and the more soluble peptide 4N1K (Lys-ArgPhe-Tyr-Val-Val-M-Lys-Lys) induce aggregation 19 and spreading of platelets on immobilized fibronectin and collagen. 15,18 The ability of the C-terminal peptide of TSP1 to modulate integrin function depends on its interaction with IAP, since spreading of platelets on fibrinogen and collagen was decreased after treatment with an antifunctional IAP antibody and in platelets from mice deficient in IAP.…”
Section: Introductionmentioning
confidence: 99%